THE DEVELOPMENT OF AN EXPERTISE LOCATOR SYSTEM (ELS) FOR ORGANIZATIONS - ISHAK, AIDA NURSABRINA ISMA (Universiti Teknologi PETRONAS, 2020)
Expert is one of the major assets in an organization since they are professionals who have acquired knowledge and skills through study and practices over the years, field or subject, to the extent that his or her opinion may be helpful in fact finding, problem solving and understand of a situation. The common ways of locating expertise in an organization is through the employee directory; however, this method has a disadvantage where the employee directory itself does not provide enough information needed in an organization. Due to this disadvantage, it is necessary to develop an appropriate Expertise Locator System (ELS) that eases the location of expertise in an organization. Completion of this study requires two-phased methodology which is the early studies and system development phases. During the early studies phase, literature review and surveys will be conducted to obtain brief information regarding this topic. The survey utilizes an anonymous Likert scaled questionnaire. Using the data obtained from the survey, ELS will be designed for construction services organizations. For system development, Waterfall methodology will be implemented for the System Development Life Cycle (SDLC) technique and with that this project will undergo four phases which are Planning, Analysis, Design and Development & Testing. PHP, MySQL and XAMPP will be utilized in enhancements of Expertise Locator System (ELS).